Sprawa kryptonim „Działacz”. Inwigilacja środowiska białoruskiego w Szczecinie na przełomie lat pięćdziesiątych i sześćdziesiątych ubiegłego stulecia - Słabig, Arkadiusz (Pamięć i Sprawiedliwość, 2011)
This article looks at the problem of surveillance of the Belarusian activists’ circle in Szczecin during the 1950s–1960s. Young Belarusian from the Bialystok region set up, in the spring of 1957, a regional branch of the Belarusian Social and Cultural Society [Białoruskie Towarzystwo Społeczno-Kulturalne, BTSK]. Michał Artyszewicz, a student of the University of Technology, was chosen as its first chairman. During a favourable period of time of the Khrushchev Thaw, Belarusian activists started integrating with each other and propagating their native culture. Not only did they manage to establish contact with many compatriots living at home and in exile but also they were able to acquire a lot of books and newspapers such as: widely popular weekly Niwa (published under the auspices of the BTSK Executive Board in Bialystok) and Baćkauszczyna (appearing in Munich). But from the very beginning Szczecin’s activists encountered many difficulties. To some extent, those disadvantages resulted from the „experimental”character of the Society and from the simple fact of being engaged in its activity far away from the territories inhabited by Belarusians. What is more, a direct consequence of a small number of the BTSK members were both – lack of financial allocation to the BTSKs regional branch from the national budget as well ashaving no own premises. In such circumstances, the existence of the Belarusian Society in Szczecin depended solely on the degree of involvement of its leaders. Their removal from the BTSKs leadership meant the end of its activity.This situation was deliberately used by the security service agents who put Artyszewicz under long-standing pressure. By carrying out operational activity code-named “Działacz” [“Activist”] they tried to recruit him as a secret collaborator or at least to isolate him from the Belarusian circle. Due to the fact that Artyszewicz maintained close ties with Belarusian activists in the West, security agents wanted to use him to penetrate the emigrants’ circles in exile. The alleged “nationalist activity” of Artyszewicz was only a pretext to control both him and other BSTKs members. To make this operation possible, apart from agent’s network, it was also necessary to use representatives of the administrative authority.Eventually, security service agents managed to liquidate the regional branch of the BSTK in Szczecin despite of the fiasco of their plan to conduct operational activity against Belarusian circles operating behind the Iron Curtain. Polish reality of the “little stabilisation”-time did not accept the existence of social structures which differed from those promoted by the Polish state.